Beyond the Proxy Vote: Dialogues Between Shareholder Activists and Corporations - Logsdon, Jeanne M. (Journal of business ethics, 2009)
The popular view of shareholder activism focuses on shareholder resolutions and the shareholder vote via proxy statements at the annual meeting, which is treated as a “David vs. Goliath” showdown between the small group of socially responsible investors and the powerful corporation. This article goes beyond the popular view to examine where the real action typically occurs – in the Dialogue process where corporations and shareholder activist groups mutually agree to ongoing communications to deal with a serious social issue. Use of the capitalized word “Dialogue” is intended to distinguish this formal process between corporations and shareholders from all the other forms of dialogue or two-way communication exchanged between a corporation and its stakeholders. The phenomenon of Dialogue between a corporation and dissident shareholders has not been analyzed in the academic literature or in the popular press because it occurs behind the scenes and out of sight from media scrutiny. Yet this is where a great deal of social change initiated by shareholder activists is negotiated. This article contributes both theoretically and empirically to the study of Dialogues between shareholder activists and corporations. We explain how Dialogues occur in the context of the shareholder resolution process and examine two Dialogues that focus on international labor issues in two industries. Then data on Dialogues during the period, 1999–2005, from the Interfaith Center on Corporate Responsibility are analyzed. This research contributes to knowledge about the Dialogue process and the emerging literature on corporation–stakeholder engagement.